Integrated management systems : a practical approach to transforming organizations - Lee, Thomas H., 1923-2001 (Wiley operations management series for professionals., 1999)
"In 1993, the Center for Quality of Management embarked on a six-year study of how organizations improve throughout America. Contrary to expectations, the authors found that successful systems of management differed radically."--BOOK JACKET. "Yet at the core of each was something universal and powerful: Each organization had developed its own particular way of executing the scientific method. Each had found its own ways of gathering data, developing theories, testing the theories, and finally documenting and sharing results."--BOOK JACKET. "In Integrated Management Systems, authors Lee, Shiba, and Wood explore the lessons learned from the CQM study. They explain how managers can create their own integrated management systems. They reveal the weaknesses that prevent effective integrated management systems from emerging in America. And they describe key ideas and tools managers can use in developing their own systems."--BOOK JACKET.